Roman Jasinsky as Icare, in Icare, The Original Ballet Russe, Australian tour, His Majesty's Theatre, Melbourne, May 1940 (6) - Hall, Hugh P.; Lifar, Serge, 1905-1986.; Nolan, Sidney, Sir, 1917-1992. (1940)
One of a collection of photographs taken by Hugh P. Hall of 28 ballet productions performed by the Covent Garden Russian Ballet (toured Australia 1938-1939) and the Original Ballet Russe (toured Australia 1939-1940). These are the second and third of the three Ballets Russes companies which toured Australasia between 1936 and 1940. The photographs were taken from the auditorium during a live performance in His Majesty's Theatre, Melbourne and mounted on cardboard for display purposes. For conservation and storage, the photographs have been demounted. The original arrangement of the photographs has been recorded, and details are available from the Pictures Branch of the National Library.
From: Icare : choreographic legend in one act / ballet and rhythms by Serge Lifar ; orchestrated by Antal Dorati.
Inscription: "4Y/25".
Part of the collection: Hugh P. Hall collection of photographs, 1938-1940.
Condition: fair, silvering.
Choreography by Serge Lifar ; scenery and costumes by Sidney Nolan.
Also available online
Keywords: His Majesty's Theatre (Melbourne, Vic.) -- Photographs; Original Ballet Russe -- Performances -- Photographs; Icare (Choreographic work) -- Photographs; Ballet dancers -- Photographs; Ballet -- Australia -- Photographs; Ballets Russes in Australia